THE MISSION-BASED MANAGEMENT PRACTICES IN NON-PROFIT ORGANIZATIONS IN ALBANIA - Hasaj, Alkida; Kruja, Drita (European Scientific Journal, ESJ, 2012)
The non-profit sector is very important for the whole scheme of a country life. Dozens of non-profit organizations actually operate in Albania. During the last 20 years there has been a significant increase in the number of non-profit organizations, because of the rapid changes in the environmental conditions. Regardless the increase in the number of these organizations, the economic challenges in the last decade had a huge influence in their ability to survive. For this reason the non-profit sector states the financial capacity as its greatest challenge. This new economy would give rise to a decline in the survival of many non-profit organizations, especially those that relied solely on government and other support. The purpose of this research is to examine whether or not the mission-based management practices suggested by Brinckerhoff had any relationship to revenues in non-profit organizations. Researchers such as Brinckerhoff postulated that non-profits must incorporate for-profit business practices into their organizational strategies (like strong marketing focus, etc) in order to adapt to the financial changes taking place in the non - profit sector. The data to conduct this study were collected from some non-profit organization in Albania using a questionnaire which they filled in by themselves. The survey questions focused specifically on each of the ten mission-based management practices which required participants to indicate whether or not any of the mission-based management practices were used. The data gathered illustrate that there appears to be a link between organizational capacity, for-profit management practices, and successful non-profit organizations. The concepts of marketing, finance, auditing and strategic planning were associated with economic thought and therefore not an area of great importance to the non-profit sector.